Mechanical Performance and Anti-Fungal and Anti-Algal Properties for Teakwood/Parawood/PVC Composites in UV-Weathering and Seawater Immersion Conditions - Sirichai Kanking; Tawich Pulngern; Vichai Rosarpitak; Narongrit Sombatsompop (BioResources, 2023)
This work examined teakwood and parawood in wood/poly(vinyl chloride) composite (WPVC) materials under UV-weathering and seawater immersion. The mechanical properties as well as anti-fungal and anti-algal performance were considered. Teakwood and parawood (a rubberwood product) in WPVC materials at ratios of 0:100, 20:80, 40:60, 50:50, 60:40, 80:20, and 100:0 were investigated. UV-weathering ageing periods of 0 to 32 days and seawater immersion periods of 0 to 90 were studied. Aspergillus niger TISTR 3012 and Chlorella vulgaris TISTR 8580 were used as marine fungi and marine algae, respectively. Higher parawood content (in formulations of 0:100, 20:80 and 40:60) in WPVC composite materials enabled better mechanical properties than those of higher teakwood content (in formulations of 60:40, 80:20 and 100:0). Seawater immersion caused more deterioration of WPVC composite materials than UV-weathering ageing. Both anti-microbial agents and wood particles are potentially used in WPVC composite materials for anti-microbial properties, including the percentage reduction of fungal and algal growth. Increasing UV-weathering ageing and seawater immersion periods decreased the percentage reduction of fungal growth, but increased the percentage reduction of algal growth in WPVC composite materials. The results suggested higher parawood content (in a formulation of 20:80) for WPVC composite materials for coastal environment applications.